INTRODUCTION OF NEW FISH SPECIES IN BORAČKO LAKE OVER THE LAST 20 YEARS (Works of the Faculty of Agriculture and Food Sciences University of Sarajevo, 2026)
Boračko Lake is a natural mountain and glacial lake located at the base of the Prenj mountain, at an elevation of 397 meters. From the ichthyological aspect, this lake was originally of a salmonid character, inhabited exclusively by lake trout. However, over the past few decades, the ichthyofauna of this lake has been significantly changed due to the introduction of other fish species. Ichthyological research conducted at Boračko Lake in 2003, 2011 and 2018 revealed the presence of several new fish species, predominantly cyprinids (fish from the order Cypriniformes). Only a small number of individuals of salmonid fish species were registered. Ichthyological research conducted in 2023 confirmed the presence of several new fish species, which were not registered in earlier research. Today, 11 fish species live in Boračko Lake, among which the most numerous are cyprinids (7 species) and they make up 75.3% of the lake’s total ichthyopopulation, while salmonids represent two species with a total share of 6.9%. The rest of the ichthyopopulation of this lake is made up of pike-perch with a share of 14.4%, while Neretva spined loach participates with a share of 3.4% of the total ichthyopopulation. In the coming period, a systematic approach is needed to address the issues through selective fishing of non-native (allochthonous) and invasive fish species in order to preserve, protect and restore the populations of indigenous species.